Implementasi Praktik Layanan Pendidikan untuk Mendukung Literasi dan Numerasi Anak pada Masa Transisi dari Pendidikan Anak Usia Dini ke Sekolah Dasar - Siti Nurkhasanah; Yuli Kuriawati Sugiyo Pranoto; Ali Formen (Postgraduate, University of Mataram, 2025)
This study aims to analyze the implementation of educational service practices that support children’s literacy and numeracy during the transition from Early Childhood Education (ECE) to Primary School, as well as to identify the supporting and inhibiting factors influencing this process. A descriptive qualitative approach was employed through classroom observations, in-depth interviews, and document analysis in schools implementing the Joyful Transition from ECE to Primary School program. The collected data were analyzed using the Miles, Huberman, and Saldaña interactive model. The results revealed three main themes. First, effective transition practices are supported by strong collaboration between ECE and primary school teachers, principal leadership, and active parental engagement. Second, play-based and science-integrated learning strategies enhance children’s literacy, numeracy, and socio-emotional development through contextual and exploratory learning experiences. Third, several challenges were identified, including limited learning resources, inconsistent perceptions of children’s academic readiness, and insufficient professional training related to transition policies. The discussion indicates that these challenges can be mitigated through reflective dialogue, peer mentoring, and the use of locally available learning materials. In conclusion, sustainable and joyful transition services require continuous teacher capacity building, pedagogical alignment between educational levels, and consistent policy support to ensure inclusive, meaningful, and developmentally appropriate learning experiences for all children.